75 Incidence of lymph node metastasis in apparent early stage endometrioid ovarian carcinoma. (13th November 2020) - Nasioudis, D; Latif, N; Haggerty, A; Cory, L; Giuntoli, RL; Kim, SH; Morgan, MA; Ko, EM
Abstract : Introduction: Aim of the present study was to evaluate the incidence of lymph node metastasis among patients with apparent early stage endometrioid ovarian carcinoma (EOOC). Methods: Patients with apparent early stage EOOC, with known tumor grade and substage diagnosed between 2004–2015 were drawn from the National Cancer Database. Performance of lymph node sampling/dissection (LND) and incidence of LN metastases were evaluated from the pathology report. Results: A total of 9725 patients with apparent early stage EOOC were identified; 44.4%, 40.5% and 15.1% had grade 1, 2 and 3 tumors respectively. 7480 (76.9%) underwent LND with a median of 12.5 LNs removed. The overall incidence of LN metastasis was 2.2%; specifically, 1.2% for grade 1, 2.2% for grade 2, and 5.1% for grade 3 tumors (p<0.001). For patients with apparent stage IA disease, LN metastases were identified in 0.7%, 1.7%, and 4.9% of grade 1, 2, and 3 cases, respectively, p<0.001. For patients with apparent stage IC disease, LN metastases were identified in 2%, 2.6%, and 5.6% for those with grade 1, 2, and 3 cases, respectively. After controlling for substage, patients with grade 2 tumors were nearly twice (OR: 1.78, 95% CI: 1.20, 2.63), and patients with grade 3 tumors were nearly four times (OR: 4.1, 95% CI: 2.74, 6.22) as likely as those with grade 1 tumor to have LN metastases. Conclusions: The incidence of LN metastasis for patients with grade 1 and 2 EOOC is overall low. LND should be considered for patients with grade 3 tumors.